Nonlinear Responses of a Rotor-Bearing-Seal System with Pedestal Looseness. (2nd September 2021) - Lin, Junzhe; Zhao, Yulai; Wang, Pengfei; Wang, Yuanyuan; Han, Qingkai; Ma, Hui
Abstract : In this paper, a pedestal looseness fault model of a rotor-bearing-seal system is established. Under two working conditions of the same direction eccentricity (Working Condition 1) and reverse eccentricity (Working Condition 2), rotor orbits, vibration waveforms, spectrum cascade, and Poincaré maps are used to study the dynamic characteristics of the system when the sliding bearing support is loosened. The influence of speed, the unbalance of two discs, the looseness clearance, and the mass of bearing support on system characteristics are analyzed. The study found that Working Condition 2 is more likely to cause looseness of the bearing support. Moreover, for the rotor system in this paper, the pedestal looseness fault is more likely to occur near the second-order critical speed. Through analysis of the spectrum, it is found that the spectrum of the looseness fault will show multiple frequencies or continuous spectra, and the rotor orbits will appear "cylindrical."